Efektifitas ekstrak kunyit (Curcuma longa) 6,96% dalam penyembuhan Stomatitis Apthousa Recurrent (SAR) Minor - Wendy Wendy; Florenly Florenly; Mellisa Sim (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2019)
Background: Stomatitis Apthousa Recurrent (SAR) Minor is one of the oral cavity ulcer disease which most often found. The impact of this disease can interfere with the comfort and quality of life as well as talk, chew, swallow, and so forth. Stomatitis Apthousa Recurrent (SAR) Minor had clinical features such as round or oval ulcers coated with pseudomembrane and surrounded by erythema halo. Turmeric is a medicinal plant which can accelerate the healing process SAR Minor. Active substance such as curcumin, saponins and tannins on turmeric has an important role in accelerating the healing process SAR Minor such as antioxidants. Objective: To see effectivity of turmeric (Curcuma longa) 6,96% in SAR Minor healing process. Method: This research is an experimental research design one group pretest posttest design. A total of 16 subjects aged between 19-21 years of research that consists of 8 control group and 8 treatment group who experienced SAR Minor. Gel turmeric (Curcuma longa) is used for 5 consecutive days. Observed and measured the size of ulcers and erythema halo at baseline, day 1, 3rd and 5th. Result: Based on research conducted, there is a significant difference (P <0.05) and erythema halo ulcer size before and after the gel extract turmeric (Curcuma longa) 6.96% in the treatment group. Conclusion: Extract Turmeric (Curcuma longa) 6.96% effective in reducing the size of the healing of ulcers and erythema halo.sehingga Apthousa Stomatitis Recurrent (SAR) Minor takes shorter.